2016
DOI: 10.19082/2475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processed Honey and Royal Jelly on Cancer-Related Fatigue: A Double-Blind Randomized Clinical Trial

Abstract: BackgroundCancer-related fatigue (CRF) is experienced by 50% to 90% of cancer patients and can severely affect their quality of life and functional capacity. Several randomized trials have recommended various ways to alleviate the symptoms of CRF with or without recourse to medications.ObjectiveThe aim of this study is to evaluate the effectiveness of processed honey and royal jelly on the symptoms of CRF in cancer patients who are undergoing hormone therapy, chemotherapy, chemo-radiation, or radiotherapy.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
2
18
1
5
Order By: Relevance
“…A double-blind randomized clinical trial was performed to evaluate the effectiveness RJ on the symptoms of cancer-related fatigue in patients administered anti-cancer therapies [ 63 ]. In this trial, 52 patients were invited into two groups: the study group was treated with processed honey and RJ ( n = 26) and the control group was treated with pure honey ( n = 26); supplements of 5 mL were administered twice per day for 4 weeks.…”
Section: Activity Of Royal Jelly Against Cancer Therapy-induced Tomentioning
confidence: 99%
See 1 more Smart Citation
“…A double-blind randomized clinical trial was performed to evaluate the effectiveness RJ on the symptoms of cancer-related fatigue in patients administered anti-cancer therapies [ 63 ]. In this trial, 52 patients were invited into two groups: the study group was treated with processed honey and RJ ( n = 26) and the control group was treated with pure honey ( n = 26); supplements of 5 mL were administered twice per day for 4 weeks.…”
Section: Activity Of Royal Jelly Against Cancer Therapy-induced Tomentioning
confidence: 99%
“…In this trial, 52 patients were invited into two groups: the study group was treated with processed honey and RJ ( n = 26) and the control group was treated with pure honey ( n = 26); supplements of 5 mL were administered twice per day for 4 weeks. All three scores of fatigue and performance status in the study group were significantly better than those in control group [ 63 ]; however, the authors indicated that further clinical trials with a larger number of patients and a longer duration of intervention are necessary to clarify the role of RJ in managing cancer-related fatigue, because their study populations included a variety of malignancies and treatments. In addition, we should note that honey and RJ but not only RJ, was used in this clinical trial.…”
Section: Activity Of Royal Jelly Against Cancer Therapy-induced Tomentioning
confidence: 99%
“…Composition of RJ includes many important compounds such as proteins, lipids, essential amino acids, minerals, vitamins, sugars, nucleic acids, enzymes, hormones, phenols (SUZUKI et al, 2008;KARADENIZ et al, 2011;ORŠOLIĆ, 2013). Due to its complex composition, RJ has demonstrated various pharmacological activities: antitumor, anti-inflammatory, antioxidant, antibiotic, immunomodulatory, hypotensive, antihypercholesterolemic, hypoglycemic, antiallergic, antiaging, hepatoprotective, and many other (IZUTA et al, 2009;PAVEL et al, 2011;SUGIYAMA et al, 2012;SUPABPHOL and SUPABPHOL, 2013;MOFID et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, complementary medicine can be a valuable choice in order to ameliorate the symptoms with a minimum of side effects. According to Mofid et al [ 53 ], up to 50% of cancer patients experience cancer-related fatigue, and the administration of both royal jelly and processed honey can alleviate the symptomatology. They administered 5mL of royal jelly and processed honey twice daily to 26 patients, and compared the results with those obtained by 26 patients, which received only 5 mL of honey, under the same scheme, for one month.…”
Section: Studies Of Royal Jelly As a Beneficial Therapeutic Agent mentioning
confidence: 99%